Dynamic status of metabolically healthy overweight/obesity and metabolically unhealthy and normal weight and the risk of type 2 diabetes mellitus: A cohort study of a rural adult Chinese population. Issue 1 (January 2018) - Wang, Bingyuan; Zhang, Ming; Wang, Shu; Wang, Chongjian; Wang, Jinjin; Li, Linlin; Zhang, Lu; Ren, Yongcheng; Han, Chengyi; Zhao, Yang; Zhou, Junmei; Wang, Guo'an; et al.
Highlights: The first prospective cohort to explore dynamic status of MHO/MUNW in Chinese people. Dynamic status of MHO/MUNW influence diabetes outcome at follow-up. Risk of diabetes was not increased for participants with stable MHO and transformation from MUNW to healthy status. Risk of diabetes was increased for participants from MHO transformed to unhealthy status. The results were consistent when analyses were restricted to participants without baseline impaired fasting glucose level. Summary: Objective: We aimed to determine dynamic status of metabolically healthy overweight or obesity (MHO) and metabolically unhealthy and normal weight (MUNW) and the risk of incident type 2 diabetes mellitus (T2DM). Methods: Body mass index and metabolic health were assessed on 11, 865 eligible participants ≥18 years from 6-year follow-up cohort study of a rural Chinese population. Participants were classified as metabolically healthy and normal weight (MHNW), MHO, MUNW and metabolically unhealthy overweight or obesity (MUO) at both baseline and follow-up examinations. Hazard ratio (HR) and 95% confidence interval (CI) were used to assess baseline and their changes of BMI-metabolic status and the risk of incident T2DM. Results: Risk of T2DM was increased for all participants with baseline MHO, MUNW, and MUO (adjusted HR 1.94, 95% CI 1.33–2.81; 3.10, 95% CI 2.19–4.39; and 6.63, 95% CI 4.94–8.90, all P < 0.001, respectively). However, risk of T2DM was increased for participants with transformation from MHO to MUO (4.52, 95% CI 2.42–8.47, P < 0.001) as compared with stable MHNW, but not stable MHO (0.53, 95CI 0.20–1.40, P = 0.20). Risk of T2DM did not differ between participants with transformation from MUNW to metabolically healthy and those with stable MHNW ( P > 0.05), but was increased with stable MUNW (5.78, 95% CI 3.15–10.62, P < 0.001). The results were consistent when analyses were restricted to participants without baseline impaired fasting glucose level. Conclusions: Our findings provide understanding for differentiating high-risk individuals for incident T2DM in Chinese population.